Message - Audu-Peter, Professor Dr. Jennifer Drambi (Universal Journal of Pharmaceutical Research, 2021)
For academics and researchers, the choice of the right journal to disseminate their research findings to as wide an audience and expert as possible is vital to their success. This is especially important when new discoveries, information and addition to knowledge need to be disseminated as fast as possible. Authors typically look for journals that have: a). Competent, diverse and internationally spread editorial board; a journal run by two or three persons would not provide the needed diverse expertise especially where manuscripts are received from such diverse specialties in a particular field. b). Author friendly and supportive editorial office without compromising quality; with clear guidelines or instructions for authors. c). A well-designed cover with good and consistent formatting and informative masthead; easy to navigate and identify its essential contents, easy to cite and share content accurately such that it is easier for librarians and educators to access. d). Frequent output and accessible, qualitative, sustainable e). High visibility and citation The incentives for choosing a journal are: Turn-around times - how long does it take from submission to review decision to reach author(s)? The faster the better How clear are information relating to submission? Does journal have room for variety of reports? (such as research, short communication, review, commissioned and opinion) How transparent is the review process (assessed by journal transparency in publishing number of received articles, rejections, revisions and acceptance. It should also declare the topics that are most accepted and rejected UJPR aims to satisfy every author, by having the best peer reviewers, editorial office and a broad spectrum of experts in pharmaceutical research bringing their wealth of knowledge from diverse backgrounds.